Comparative efficacy of autologous platelet rich plasma and conventional dressing in the management of chronic ulcers - Bishnoi, Anuj; Gupta, Jagdish; Verma, Neeraj; Bishnoi, Monika; Chauhan, Pallavi; Chaudhary, Mayank (International Surgery Journal, 2024)
Background: Chronic ulcers pose a major global healthcare challenge. The use of platelet-rich plasma (PRP) for treating these wounds has garnered interest because of its potential healing benefits. Objective were to determine the effect of autologous PRP therapy on the percentage of surface area reduction/healing in chronic ulcers. Methods: This randomized controlled trial was conducted at the department of general surgery of M.M. institute of medical sciences and research (M.M.I.M.S.R.) Mullana, Ambala from May 1, 2023, to April 30, 2024. Patients aged 18-80 years of either gender with chronic ulcers were enrolled. Patients were randomly allocated to the PRP group and control group. PRP group was administered autologous PRP once in two weeks for 6 weeks after debridement, while for the control group conventional saline dressings were done after debridement. Final assessment was done at 8 weeks. Results: Of the 60 patients, the mean age was 53.90±11.23 years. There were 49 (82%) males and 11 (18%) females. At 8 weeks, the PRP group achieved 83.78% (SD=2.99) reduction in surface area of ulcers, whereas the control group had a 57.78% (SD=1.32) reduction in surface area of ulcers, with a p=0.0000 indicating a significant difference. The small sample size and 56-day follow-up period are insufficient to assess long-term treatment effects. Conclusions: A better outcome of PRP was observed compared to conventional dressing in patients with chronic non-healing ulcers.